Evaluation of Power Distribution based on Power Losses on Transmission Interconnection - Agustina, Mega; Afandi, A. N (Frontier Energy System and Power Engineering, 2019)
This paper discusses the analysis of continuity of power delivery and network losses in the scenario of adding 150 kV to the Malang Raya transmission network. The discussion in this paper is based on the increasing load growth conditions in Malang Raya and the condition of the Malang 150 kV main system which is centralized in the Kebonagung Substation so that a scenario of adding 150 kV transmission network interconnection is needed to increase the capacity, reliability, and improvement of the Malang Raya system. Based on the simulation results before the scenario of adding 150 kV transmission network losses in the poor 150 kV main system by 0.02 MW, whereas after the scenario of adding 150 kV transmission network the overall losses in the 150 kV main unfortunate main system were 0.009 MW.